Recent genetic studies in cowpea - Singh, B.B. (2002)
A number of recent studies have added further information on the genetics of important traits in cowpea. These include inheritance of qualitative traits such as plant pigmentation; flower color; seed color; seed coat texture; resistance to rust, scab, smut, nematode, severe mosaic virus, Striga, Alectra, aphid, bruchid, heat; drought tolerance; and male sterility, and quantitative traits such as protein content, seed size, seed yield, and fodder quality. A few studies on linkage and mapping have also been conducted. The gene symbols from recent studies and earlier reports have been collated in a classified and trait-based gene index for easy reference. While reviewing the past genetic work, obvious gaps needing further studies have been indicated.